FASILITAS DAN PEMANFAATAN RUANG TERBUKA HIJAU PUBLIK KELURAHAN PONDOK KELAPA (STUDI KASUS TAMAN MAJU BERSAMA PONDOK KELAPA) - Annisa Rizky Utami; Rosmawita Saleh (Jurnal Pendidikan Teknik Bangunan, 2022)
Indonesia's population is increasing followed by construction of facilities and infrastructure, one of which is in the scope of the environment such as public RTH, but facilities and benefits do not always run according to the provisions. Quantitative descriptive study is used in this research, in order to explain the conditions for the use of the public RTH and the condition of the facility. This research uses questionnaire research methods and ekisting surveys The facilities and utilization at TMB Pondok Kelapa have not been utilized as their functions. Many facilities are still damaged and need to be repaired and the pattern of utilization of community facilities is also not as it should be.